Development of New Technologies for Cattle Breeding Systems Taking Into Account Sustainable Environmental Conditions (Agricultural Engineering, 2018)
Properly designed housing buildings, with regard to reduction of a negative influence on environment, are necessary for ensuring sustainable development in agriculture. The objective of this paper was to show the results of environmental conditions research on high milk yield dairy cattle in different housing systems. Temperature and relative humidity of air and concentrations of harmful gases − ammonia and carbon dioxide accompanying them were investigated.